Evaluasi Program Pendidikan - Iqbal, Muhammad; Marpaung, Wardatun Thaibah; Maulida, Sifa; Oktaviani, Dita; Widyana, Tasya (Indo-MathEdu Intellectuals Journal, 2024)
A comprehensive evaluation aims to identify the strengths and weaknesses of the program, thus allowing for informed decision-making for improvement and development. This study aims to analyze the concepts, objectives, principles, steps, supporting factors, inhibiting factors, and solutions to overcome inhibiting factors in the implementation of educational program evaluation. The research method used is a literature review, with a focus on literature review analysis that discusses the concepts and steps of evaluating educational programs, as well as factors that need to be considered in the evaluation. The results show that the evaluation of educational programs has the goal of assessing program effectiveness, identifying areas of improvement, and encouraging improvement in the quality of education. The evaluation of educational programs should be guided by the principle of objectivity and focus on the goals of the program. The steps that must be taken in the evaluation of educational programs include the preparation and implementation as well as monitoring of the evaluation of educational programs. Supporting factors for the evaluation of educational programs include clear and firm policies from the government and educational institutions. This policy includes evaluation standards that must be met, methodologies used, and evaluation implementation schedules Factors that hinder the evaluation of educational programs include a lack of resources, both in terms of finance and competent experts.